LEGAL RELATIONS BETWEEN THE INVESTIGATOR AND THE PROSECUTOR IN THE COURSE OF COVERT INVESTIGATIVE (DETECTIVE) ACTIONS: A THEORETICAL AND LEGAL ANALYSIS - Кропивка, Р. О. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2023)
Abstract. The article examines the legal relations between the investigator and the prosecutor in the course of conducting covert investigative (detective) actions (CIDA), as well as the doctrinal approaches to the definition of the concept and essence of covert investigative (detective) actions. The purpose of the article is a theoretical and legal analysis of the legal relationship between the investigator and the prosecutor when conducting a criminal investigation as a means of obtaining evidence and developing scientifically based proposals for their improvement. The author emphasizes that legal regulation of the CIDA should ensure a balance between the effectiveness of law enforcement activities and the observance of human rights and freedoms guaranteed by the Constitution and international legal acts. In this context, the legal relationship between the investigator and the prosecutor, who play a key role in the process of planning, organising, monitoring and evaluating the results of the CIDA, deserves special attention. The investigator, as the initiator of most covert measures, is responsible for their validity and legality, while the prosecutor supervises compliance with legal norms, ensuring the legitimacy of such actions. It is indicated that an effective, complete and impartial investigation of criminal offences largely depends on the coordinated interaction between the investigator and the prosecutor, who are the key participants in criminal proceedings on the part of the prosecution. Coherent cooperation between the investigator and the prosecutor is a prerequisite for the successful fulfilment of the tasks set out in Article 2 of the Criminal Procedure Code of Ukraine, in particular, ensuring proper pre-trial investigation, observance of human rights and legitimate interests of the participants to the proceedings. The article examines the practice of national courts and the ECHR on certain issues of the pre-trial investigation. The author identifies typical violations committed by investigators and prosecutors in the course of conducting pre-trial investigation and suggests ways to eliminate them. It is concluded that the final assessment of the results of the CIDA for their further use in the evidence base is possible only after a thorough verification and confirmation of the data obtained by other procedural means. This necessitates close cooperation between the investigator and the prosecutor, where each performs clearly defined functions, interacting within the framework of the law and professional ethics.

Анотація. У статті досліджено правовідносини слідчого і прокурора при провадженні НСРД, а також доктринальні підходи до визначення поняття та сутності НСРД. Метою статті є теоретико-правовий аналіз правовідносини слідчого і прокурора при провадженні НСРД як засобів отримання доказів й вироблення науково обґрунтованих пропозицій щодо їх удосконалення. Наголошено, що правове регулювання проведення НСРД має забезпечити баланс між ефективністю правоохоронної діяльності та дотриманням прав і свобод людини, гарантованих Конституцією та міжнародними правовими актами. У цьому контексті особливої уваги заслуговують правовідносини між слідчим і прокурором, які відіграють ключову роль у процесі планування, організації, контролю та оцінки результатів НСРД. Слідчий, як ініціатор більшості негласних заходів, несе відповідальність за їх обґрунтованість і законність, тоді як прокурор здійснює нагляд за дотриманням правових норм, забезпечуючи легітимність таких дій. Вказано, що ефективне, повне та неупереджене розслідування кримінальних правопорушень значною мірою залежить від узгодженої взаємодії між слідчим і прокурором, які виступають ключовими учасниками кримінального провадження зі сторони обвинувачення. Злагоджена співпраця між слідчим і прокурором є необхідною передумовою для успішного виконання завдань, визначених у ст. 2 Кримінального процесуального кодексу України, зокрема щодо забезпечення належного досудового розслідування, дотримання прав людини та законних інтересів учасників процесу. Вивчено практику національних судів та ЄСПЛ щодо окремих питань провадження НСРД. Встановлено типові порушення, які допускають слідчі та прокурори при проведенні НСРД, запропоновано шляхи їх усунення. Зроблено висновок, що остаточна оцінка результатів НСРД для їх подальшого використання у доказовій базі можлива лише після ретельної перевірки та підтвердження здобутих даних іншими процесуальними засобами. Це обумовлює необхідність тісної співпраці між слідчим і прокурором, де кожен виконує чітко визначені функції, взаємодіючи в рамках закону і професійної етики.
ПРАВОВІДНОСИНИ СЛІДЧОГО І ПРОКУРОРА ПРИ ЗДІЙСНЕННІ НЕГЛАСНИХ СЛІДЧИХ (РОЗШУКОВИХ) ДІЙ: ТЕОРЕТИКО-ПРАВОВИЙ АНАЛІЗ
Keywords: covert investigative (detective) actions; pre-trial investigation; legal relations; prosecutor; investigator.; негласні слідчі (розшукові) дії; досудове розслідування; правовідносини; прокурор; слідчий; докази; доказування.